Investigation of temperature effect on pressure measurement using Raman peak shift by variable temperature and pressure Raman experiment. (3rd July 2022) - Yu, Guoyang; Zeng, Yangyang; Wu, Honglin; Song, Yunfei; Zheng, Xianxu; Tan, Duowang; Wu, Qiang; Yang, Yanqiang
Abstract: The variable temperature and pressure Raman experiments of triamino trinitrobenzene (TATB) have been performed to investigate the temperature effect on the pressure measurement using the Raman peak shift. The experimental results indicate that the temperature has an approximately linear relationship with the Raman peak shift but no significative effect on the pressure dependence of the Raman peak shift. And then, the results of TATB under laser‐driven shock wave are chosen to illustrate the temperature effect in the shock pressure measurement. The absolute differences of the pressure values ignoring and considering the temperature are relatively large in the period of the shock loading, but the percent changes of these two values are relatively large in the period of the shock unloading. Thus, in the pressure measurement using Raman peak shifts, the temperature effect on the Raman peak shift needs to be considered, especially for the case of the shock unloading. Abstract : The variable temperature and pressure Raman experiments of triamino trinitrobenzene (TATB) have been performed to investigate the temperature effect on the pressure measurement using the Raman peak shift. In the pressure measurement using Raman peak shifts, the temperature effect on the Raman peak shift needs to be considered, especially for the case of the shock unloading.